STRATEGI PEMIMPIN DALAM MENDORONG KINERJA GURU SMAN 8 KOTA BANJARMASIN - Muhammad Yuliansyah; Jarkawi Jarkawi; Murdiansyah Herman; Junaidy Junaidy (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2021)
A good teacher in the connotation of personal quality (a good teacher), or a successful teacher (a full success teacher), and an effective teacher. Now it is necessary to understand the image or profile of a teacher, to know his status in the educational community which is always changing suddenly and surprising so that, placing the role of the teacher as an agent of change and developing moral responsibility and commitment and high abstract thinking in carrying out the educational mission. In the aspect of teacher performance, the results of the initial survey show that the lack (work performance, work ability, job performance, work production, low work discipline, low creativity) as visible indicators at that time are the behaviors or actions seen by the teachers that show less performance. should.